Hip and knee net joint moments that correlate with success in lateral load transfers over a low friction surface. Issue 12 (1st December 2016) - Catena, Robert D.; Xu, Xu
Abstract: We previously described two different preferred strategies used to perform a lateral load transfer. The wide stance strategy was not used successfully on a low-friction surface, while the narrow stance strategy was successful. Here, we retrospectively examined lower extremity net joint moments between successful and unsuccessful strategies to determine if there is a kinetic benefit consideration that may go into choosing the preferred strategy. Success vs. failure over a novel slippery surface was used to dichotomise 35 healthy working-age individuals into the two groups (successful and unsuccessful). Participants performed lateral load transfers over three sequential surface conditions: high friction, novel low friction and practised low friction. The unsuccessful strategy required larger start torques, but lower dynamic moments during transfer compared to the successful strategy. These results indicate that the periodically unsuccessful strategy may be preferred because it requires less muscle recruitment and lower stresses on lower extremity soft tissues. Practitioner Summary: The reason for this paper is to retrospectively examine the joint moment in two different load transfer strategies that are used in a lateral load transfer. We found that periodically unsuccessful strategies that we previously reported may be a beneficial toward reduced lower extremity joint stresses.